Antitubercular activity of 7-methyljuglone-loaded poly-(lactide-co-glycolide) nanoparticles - Lall, Namrita (University of Pretoria, 2023)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2023.